2003
DOI: 10.1897/1551-5028(2003)022<0908:haatft>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology as a Tool for the Evaluation of Endocrine Disruption in Zebrafish (Danio Rerio)

Abstract: The importance of histology as a tool in the evaluation of endocrine disruption in fish depends on the choice and interpretation of appropriate endpoints, as is illustrated by the analysis of the effects of exposure to the estrogen 17beta-estradiol (E2) and the nonaromatizable androgen 17-methyldihydrotestosterone (MDHT). The E2 led to the disappearance of vitellogenic oocytes in the ovary and an increased area of relatively large, eosinophilic cells in the testis, which were identified as spermatogonia under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 16 publications
4
22
0
1
Order By: Relevance
“…Histological examination revealed that treatment with E2 inhibited meiotic division of spermatogonia. Similar inhibitory effects of E2 on testicular development have been reported in rainbow trout and in zebrafish showing that E2 inhibited testicular development and the progress from spermatogonia to spermatid 11,30 . Moreover, alkylphenolic compounds and synthetic estrogens such as nonylphenol, ethynylestradiol and octylphenol also had inhibitory effects on gonadal development in male teleost species 6–10 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Histological examination revealed that treatment with E2 inhibited meiotic division of spermatogonia. Similar inhibitory effects of E2 on testicular development have been reported in rainbow trout and in zebrafish showing that E2 inhibited testicular development and the progress from spermatogonia to spermatid 11,30 . Moreover, alkylphenolic compounds and synthetic estrogens such as nonylphenol, ethynylestradiol and octylphenol also had inhibitory effects on gonadal development in male teleost species 6–10 .…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies reported that estradiol‐17β (E2), which is a natural estrogen but one of the strongest endocrine disruptors in the environment, and estrogenic compounds such as synthetic estrogen and alkylphenol, are discharged from sewage in several countries 3–5 . These estrogenic compounds have disrupted fish reproduction by causing an increase of vitellogenin in serum of male fish and inhibition of testicular development 5–11 . Additionally, exposure to pulp and paper mill effluent (PME) induced masculinization in female teleosts, suggesting that androgenic compounds were contained in PME 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…The gonads can be considered as a primary target organ for exogenous compounds with estrogenic or androgenic activity. This also was observed in zebrafish exposed to 10 g/L of 17␣-methyl-dihydrotestosterone [33]. After the eggs are ovulated into the ovarian or peritoneal cavity, postovula-tory follicles remain for some time.…”
Section: Histopathologymentioning
confidence: 62%
“…Details regarding histotechnique and histological assessment have been described previously [14]. In brief, animals were fixed in Bouin's fixative for 24 h, then transferred and stored in 70% ethanol and embedded in paraffin after dehydration in a graded ethanol/xylene series.…”
Section: Histologymentioning
confidence: 99%
“…Reproduction parameters (fecundity, fertility), mortality, and growth were evaluated and integrated with VTG expression and histology, with the latter enabling evaluation of the specific pathological events of endocrine disruption [14]. The online version was corrected 12/20/06.…”
Section: Introductionmentioning
confidence: 99%